The hidden power of Photoshop CS : - Lynch, Richard (SYBEX, 2004)
The Hidden Power of Photoshop CS takes a rigorously image-focused approach starting with exercises to help you view images in terms of color and tone components. This is not just theory, but a set of practical techniques you can use to separate, modify, and recombine any image. This perspective provides an essential foundation for your work. Your guide and mentor, Richard Lynch, follows through with practical information on using Photoshop’s most advanced tools for everyday imaging tasks. Finding these often obscure features is half the trick; understanding what they’re actually for and how they work is the other.